Advanced electric drives : analysis, control, and modeling using MATLAB/Simulink - Mohan, Ned. (Hoboken, New Jersey : Wiley, 2014)
"Advanced Electric Drives utilizes a physics-based approach to explain the fundamental concepts of modern electric drive control and its operation under dynamic conditions. Gives readers a "physical" picture of electric machines and drives without resorting to mathematical transformations for easy visualization Confirms the physics-based analysis of electric drives mathematically Provides readers with an analysis of electric machines in a way that can be easily interfaced to common power electronic converters and controlled using any control scheme Makes the MATLAB/Simulink files used in examples available to anyone in an accompanying website Reinforces fundamentals with a variety of discussion questions, concept quizzes, and homework problems"--
"Comprehensive explanation of how electric drives operate under dynamic conditions"--
""3-10Â Â Â Â Summary""""Reference""; ""Problems""; ""4: Vector Control of Induction-Motor Drives: A Qualitative Examination""; ""4-1Â Â Â Â Introduction""; ""4-2Â Â Â Â Emulation of dc and Brushless dc Drive Performance""; ""4-3Â Â Â Â Analogy to a Current-Excited Transformer with a Shorted Secondary""; ""4-4Â Â Â Â d- and q-Axis Winding Representation""; ""4-5Â Â Â Â Vector Control with d-Axis Aligned with the Rotor Flux""; ""4-6Â Â Â Â Torque, Speed, and Position Control""; ""4-7Â Â Â Â The Power-Processing Unit (PPU)""; ""4-8Â Â Â Â Summary""; ""References""; ""Problems""
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: MATLAB; SIMULINK; Electric driving -- Computer simulation; Electric motors -- Mathematical models; TECHNOLOGY & ENGINEERING / Electronics / Circuits / General; TECHNOLOGY & ENGINEERING / Power Resources / Electrical; Electric motors -- Mathematical models; Electronic books; Electronic books